Scriptures' Indexical Touch. Issue 1 (3rd July 2017) - Watts, James
Abstract : Touching and holding books does not usually evoke the language of sensation. Touching a book indexes the reader in relationship to the book. Holding a book of scripture indexes a person as faithful to the beliefs and practices that are commonly associated with that scripture. In portraiture, the direction of a book's indexical function is usually clear. Scribes, professors, lawyers and politicians pose in their libraries, often with book in hand, to depict themselves as scholars. The fact that scriptures are books makes a vocabulary of textual agency available for describing their symbolic function. The indexical link between book and person gains force from the fact that books and people share the quality of interiority. We think of both books and people as material containers of immaterial ideas. Therefore, images of people with books invite viewers to consider the relationship between their invisible ideas. However, art that portrays a god or goddess holding a scripture conveys a tighter indexical relationship, often to the point of collapsing any distinction between them.